Association between cloacal exstrophy and two limited dorsal myeloschisis lesions: A case report and literature review - Abdulrahman Jafar Sabbagh; Rana Moshref; Faisal Asiri; Abdulaziz Basurrah; Abdulrahman Arafah; Jamal Kamal (Journal of Spine Practice)
Background: The term limited dorsal myeloschisis (LDM) was coined by Pang in 1993. It involves incomplete obliteration of the dorsal neural fold in primary neurulation. On the other hand, Cloacal Exstrophy is one of the most complex endodermal anomalies and is usually associated with spinal anomalies; hence, the term OEIS complex was coined (Omphalocele, Exstrophy of the cloaca, Imperforate anus, and Spinal deformities complex).